Multimorbidity in primary care: protocol of a national cross-sectional study in Switzerland. Issue 10 (28th October 2015) - Déruaz-Luyet, Anouk; N'Goran, A Alexandra; Tandjung, Ryan; Frey, Peter; Zeller, Andreas; Haller, Dagmar M; Rosemann, Thomas; Burnand, Bernard; Bodenmann, Patrick; Senn, Nicolas; Widmer, Daniel; Herzig, Lilli
Abstract : Introduction: With the ageing of the population and the general improvement of care, an increasing number of people are living with multiple chronic health conditions or 'multimorbidity'. Multimorbidity often implies multiple medical treatments. As a consequence, the risk of adverse events and the time spent by patients for their treatments increase exponentially. In many cases, treatment guidelines traditionally defined for single conditions are not easily applicable. Primary care for individuals with multimorbidity requires complex patient-centred care and good communication between the patient and the general practitioner (GP). This often includes prioritising among the different chronic conditions. Methods and analysis: The main objectives of this study are to describe the burden related to multimorbidity (disease-related burden and burden of treatment) in primary care and to identify the factors influencing it. Other objectives include evaluating patients' perception of treatment burden and quality of life, assessing factors influencing that perception, and investigating prioritisation in the management of multimorbidity from the perspectives of GPs and patients. For this cross-sectional study, patient enrolment will take place in GP's private practices across Switzerland. A convenient sample of 100 GPs will participate; overall, 1000 patients with at least three chronic health conditions will be enrolled. Data will be collected as paper-based questionnaires for GPs and delayed telephone interview questionnaires for patients. GPs will provide demographic and practice-related data. In addition, each GP will complete a paper-based questionnaire for each patient that they enrol. Each patient will complete a telephone interview questionnaire. Ethics and dissemination: This study has been approved by the research ethics committee of Canton Vaud, Switzerland (Protocol 315/14). The results of the study will be reported in international peer-reviewed journals.